PENGARUH RETURN ON INVESTMENT (ROI), CASH RATION, DEBT TOTAL ASSET, EARNING PER SHARE (EPS) DAN SIZE ATAS DIVIDEN KAS (STUDI PADA EMITEN MANUFAKTUR DI BURSA EFEK JAKARTA) - Surya, Jen (Jurnal Akuntansi Muhammadiyah, 2010)
The objective of this research is to examine and analyze the influence of return on investment (ROI), cash ratio, current ratio, debt to total asset (DTA), earning pershare (EPS), and size as independent variabel to dividen kast as dependent variabel both simultaneously an partially in manufacturing companies listed in Jakarta stock exchange (JSX). Observation periods from 2001 until 2005. The type of research used in verification research or research to verify hypothesis with simple random sampling.The object of population are manufacturing industries which listed in Jakarta Stock Exchange (JSX)Â  that itâs financial statement has information about return on investment (ROI,)Â  cash ratio, current ratio, debt to total asset (DTA), earning pershare (EPS), size and paid to dividen kast. The research samples 21 manufacturing corporation. To aimed influence of independent variable to dependent variable both simultaneously and partially use multiple regression.Result of this research show that; (1) ROI has no significant influence on dividen kast, (2) cash ratio has no significant influence on dividen kast, (3) current ratio has significant influence on dividen kast, (4) DTA has no significant influence on dividen kast, (5) EPS has a significant influence on dividen kast,(6) size has no significant influence on dividen kast, (7) simultaneously ROI, Cash ratio, current ratio, DTA, EPS and size has a significant (72%) influence on dividen kast.Â Keywords:Â  return oninvestment (ROI), Cash ratio, current ratio, debt to total asset (DTA),earning per share ( EPS), size and dividen kast.